Human Service Professionals' Practice with Families After Parental Incarceration - Hedrington Jones, Renata Aloma (2015)
Social workers and other human services professionals helping families reintegrate after parental incarceration deal with multiple issues without a model of for facilitating family resilience. The purpose of this phenomenological research study was to explore the essence of the perceived role, activities, and practices of a sample of social workers and other human service professionals engaged in the use of family group conferences (FGCs). FGCs are also referred to as restorative justice, as they inform and assist human service professionals in developing clinical interventions and best practices to support reintegration, family preservation, and stabilization. The framework for this study was built around restorative justice theory, resiliency theory, and a larger social ecological theory and focused on the use of FGCs as a developing practice within family systems and the community. The primary research questions investigated the practitioners' experiences using FGCs. Data came from interviews of participants (15) drawn from professional associations and included their own case notes and reflections. The data was sorted and analyzed with the assistance of qualitative analysis software (Atlas.Ti7) to search for themes that may assist in identifying the phenomenon. The findings suggest that the FGC model should consist of a training curriculum, consistent practice, and dedicated and committed financial resources to support programs. This study impacts social change by informing human services professionals of current best practices and may provide a model of FGCs that will help implement services to families